When “One Size Fits All” Fits None: A Commentary on the Impacts of the“Draft Canadian Breast Cancer Screening Guidelines” on Racialized Populations in Canada - Beverley Osei; Gayathri Naganathan; Juliet M. Daniel; Supriya Kulkarni; Aisha Lofters; Yinka Oladele; Leila Springer; Mojola Omole (Current Oncology)
Epidemiological data show racial and ethnic differences exist in breast cancer morbidity and mortality amongst Black, Indigenous, Asian, and Hispanic populations, with non-white females experiencing earlier age at diagnosis, more aggressive breast cancer subtypes and advanced cancer stages, and earlier mortality than white females. However, the current Canadian breast cancer screening guidelines recommend biannual screening for all females starting from age 50 to age 74 and suggest not to screen individuals aged 40–49. In May 2024, the Canadian Task Force for Preventative Health released updated draft breast cancer screening guidelines, maintaining such recommendations for screening. Both the existing and the proposed guidelines fail to account for the unique cancer burden amongst racialized populations in Canada and risk further perpetuation of existing racial and ethnic disparities by underscreening racialized females. This commentary will present data regarding racial disparities in cancer burden, highlighting the role social and biological factors play in impacting cancer risk and age of disease and presenting perspectives from stakeholder groups reflecting the impacts of current screening guidelines. Ultimately, we critique the current “one-size-fits-all” approach to breast cancer screening in Canada, emphasizing the need for adapted screening practices with the understanding that the current approaches overlook the needs of racialized Canadian populations.